Investigation on Influences of Two Discrete Methods on Galloping Characteristics of Iced Quad Bundle Conductors - Xiaohui Liu; Guangyun Min; Chuan Wu; Mengqi Cai (Advances in Civil Engineering)
The partial differential galloping equation of iced quad conductors can be transformed into an ordinary differential galloping equation by two discrete methods: one is a direct discrete method and the other is an indirect discrete method. The two discrete methods are reasonable and effective and have their own advantages and disadvantages, but whether the two different discrete methods would cause the differences in galloping characteristics of the iced quad conductor has not been studied. Based on this concept, this paper studies this problem systematically. Firstly, based on the variational principle for Hamiltonian, the partial differential galloping equation with 3DOFs of the iced quad bundle conductor is derived and then two discrete methods are used to transform the partial differential galloping equation into an ordinary differential galloping equation. One is to use a direct method to transform partial differential galloping equation into an ordinary differential galloping equation, while the other is to use an indirect method to transform partial differential galloping equation into an ordinary differential galloping equation. Secondly, based on the wind tunnel test, the three-component aerodynamic coefficients of each subconductor of the iced quad conductor are obtained, and the equivalent aerodynamic coefficients at the central axis of the quad bundle conductor are obtained by using a reasonable method. Then, the aerodynamic coefficients are fitted by Taylor rules and the aerodynamic coefficients of wind angle of attack which is 55° are used in the analysis of galloping characteristics of the iced quad conductor. Finally, based on the numerical method, the displacement response of the two discrete methods is obtained. By comparing the differences of the displacement response obtained by the two discrete methods, it is found that the two discrete methods have certain influences on the phase, frequency, and amplitude of the iced quad bundle conductor. By comparing the calculation process of these two discrete methods, it can be obtained that the calculation process of the direct discrete method is more complex and the calculation process of the indirect discrete method is simpler. By comparing the calculation results of these two discrete methods, the amplitude obtained by the indirect discrete method is bigger than that obtained by the direct discrete method, especially the amplitude in the torsional direction. The research conclusion of this paper can offer some guidance to civil and electric engineering.